Implementation Of Habituation Program Of Tadarus Al-Qur'an In Love Building Of Al-Quran At Students Of Smp Muhammadiyah 15 Sedayulawas Brondong Lamongan - Muhammad Hambal (TADARUS, 2019)
AbstractThis study aims to delve into the implementation of program habituation oftadarus Qur'an in coaching love of the Qur'an at students of SMPMuhammadiyah 15 SedayulawasBrondongLamongan. This study used aqualitative research, with descriptive approach. The process of datacollection was done by using the instrument of observation, interviews anddocumentation. The data have been collected and analyzedby the collection,reduction, and presentation of data and the conclusion in accordance withthe scope of the problem. The results of this study indicated that habituationof tadarus Qur'an program in SMP Muhammadiyah 15SedayulawasBrondongLamongan is for students to read the Qur'an heldevery morning before starting the lesson, the program of conditioningtadarus the Qur'an aims to establish thestudent Islamic character that isloving Qur'an more by reading or listening happily. Therefore, this activitybecomes a tradition that is deemed suitable for the students in religiousactivities and as a means of well habituation in daily activities in the realmof religion that led to the approach of the Qur'an. Keywords: Tadarusal-Qur’an, Habituation, Buildinglove of the al-Qur’an